Propuesta de diseño de una red inalámbrica 802.11b/g en la Universidad de Pinar del Río con análisis de cobertura y de seguridad - Bastidas Garzón, Edgar Mauricio (2010)
This work is centered in the proposal of design of a wireless network in the University of Pinar del Río (UPR) superimposed to the wired network already existent, pursuing the idea of minimizing to the maximum the shade areas, constituting an alternative so that the students and professors of the center, as well as companies or assistants to events and other activities organized by the center, they can consent to the different services that it offers the wired network, through mobile devices, guaranteeing the necessary security for the protection of the transmitted information. The proposal is limited to the educational building and the student residence being the parsonage building for a later work....